UNTHINKING AND THINKING WITH HEIDEGGER: ON NIHILISM AND THE METAPHYSICS OF CLOSURE - Jeffrey L. Bartilet (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2025)
The paper attempts to partly sketch Martin Heidegger’s project of ontology via the route of his discussion of nihilistic thought. It employs a purely hermeneutical analysis of selected texts of available literature on print and online on Heidegger, nihilism, and metaphysics. Examining a selection of his writings, the paper contends that Heidegger’s articulation of the problem of Being, of thinking, and of technology may be weaved together by looking at the nihilistic elements by which these problems where addressed. It does this by first looking at the discussion of traditional metaphysics and sciences found in Heidegger’s work, and second, because of the representational frame by which these traditions work these traditions tended to overlook the question of Being. The paper concludes by retrieving Heidegger’s retrieval of a kind thinking that is no longer calculative but meditative.